A comprehensive systematic review of pharmacological and non-pharmacological depression interventions for patients on dialysis - Ahyeon Cho; Tammy Tran; Laura Telfer; Ahmad Matarneh; Sundus Sardar; Nasrollah Ghahramani (SAGE Open Medicine)
Background: Depression affects 38%–80% of end-stage renal disease patients on dialysis, causing increased hospitalizations, treatment nonadherence, and mortality rates. While various interventions have been researched, a comprehensive assessment remains necessary to address the psychological burden effectively. Objective: To assess previous research from 2017 to 2023 on the efficacy of pharmacological and non-pharmacological interventions for depressive symptoms in this group. Methods: A systematic review was performed across PubMed, ScienceDirect, Clinical Key, and Web of Science. Citations for inclusion and abstract extraction were assessed and confirmed by two independent researchers. Inclusion criteria consisted of clinical trials, randomized controlled trials, and prospective studies written in English. We excluded studies that were review articles, case reports, or editorials, or did not examine antidepressants, exercise, or other mental health interventions in dialysis patients. To assess risk of bias, the Risk of Bias 2 and the Risk of Bias in Non-randomized Studies of Interventions tools were utilized. Depressive symptoms were measured using different scales. Results: Among 911 screened citations, 30 articles were included, involving 1815 participants across 17 countries. Publications on antidepressant medication ( n  = 4), exercise ( n  = 9), music therapy ( n  = 4), and psychotherapy ( n  = 13) were included. Conclusion: While interventions like antidepressants, intradialytic exercise, music therapy, and psychotherapy show potential for managing depression in dialysis patients, small sample sizes, lack of control groups, and short treatment durations continue to limit current studies. Future research should focus on multicenter trials with larger, more diversified populations and stronger study designs.